Pengaruh Penambahan Serbuk Biji Asam Jawa (Tamarindus indicalin) Sebagai Koagulan Untuk Menurunkan Kadar COD (Chemical Oxygen Demand) Dan TSS (Total Suspended Solid) Pada Limbah Cair Industri Kecap - Sulaiman Hamzani; Syarifudin A.; Istiqomah Istiqomah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
Abstract: Influence Of Addition Of Java (Tamarindus indicalin) Acid Seeds Powder As Coagulation To Reduce COD (Chemical Oxygen Demand) And TSS (Total Suspended Solid Levels On Liquid Waste Soy Sauce. Liquid waste soy sauce can impact on the surrounding environment such as pollution and environmental degradation. This can lead to poor water quality be unfeasible, the soil less productive, health disorders due to skin diseases and pruritus (itchy skin). One way of processing liquid waste is the addition of java acid (Tamarindus indicalin) seeds powder as coagulation to reduce COD and TSS levels in liquid waste soy sauce. This study aimed to determine the effect the utilization of java acid (Tamarindus indicalin) seeds as coagulation to decrease COD and TSS levels on liquid waste soy sauce. This study was experimental method, data obtained through test of additional Java acid seeds powder of C, sample treatment by jar test and laboratory test of COD and TSS parameters. The results of additional java acid (Tamarindus indicalin) seeds powder by dosage variation (0 g/L, 5 g/L, 7 g/L, 9 g, 11 g, and 13 g) and jar test. Its laboratory test for COD and TSS parameters before treatment respectively were 18.000 mg/L and 673 mg/L, for results after treatment had percentage decrease COD and TSS levels were 68% and 40.96% at optimal dosage obtained 9 g/L. The stastical analysis showed that there were differences in almost all doses variation.